Beta irradiation effects on impedance spectra of electrospun PEDOT:PSS nanofibres - Urfa, Yalcin; Altindal, Ahmet (INDIAN ACAD SCIENCES, 2021)
Poly(3,4-ethylenedioxythio-phene):poly(styrenesulphonate) (PEDOT:PSS) nanofibres were first prepared via electrospinning method. Microstructural arrangement of the nanofibres was investigated by scanning electron microscopy technique. Then, the effect of beta irradiation with different absorbed doses on their impedance spectra were investigated in the frequency range from 5 to 13 x 10(6). It was observed that beta irradiation leads to a considerable decrease in both real and imaginary parts of the complex dielectric function, and alternating current conductivity of the nanofibres. The obtained frequency dependent conductivity data were discussed in terms of pair approximation. It was established that, for all beta irradiation doses, the frequency dependence of the conductivity is characterized by the presence of four frequency regions with different slopes. Analysis of the impedance data revealed that chain scission via chain cross-linking and free radical formation are most likely mechanisms for changes in impedance parameters. Two clear semicircles in Nyquist plot have been successfully explained by employing two parallel R-CPE equivalent circuits in series configuration. An overall evaluation of the obtained data indicates that electrospun PEDOT:PSS nanofibres have great potential for the development of highly sensitive impedance-based beta radiation sensor.
Keywords: Electrospun; impedance spectra; chain scission; dielectric response; GAMMA-RADIATION; CONDUCTIVITY; POLYMER; PHTHALOCYANINE; FILMS; Materials Science